Preliminary Efficacy and Safety of Camrelizumab in Combination With XELOX Plus Bevacizumab or Regorafenib in Patients With Metastatic Colorectal Cancer: A Retrospective Study - Zhou, Hong; Wang, Yuehui; Lin, Yanfang; Cai, Wenjie; Li, Xiaofeng; He, Xiaomeng (Frontiers in Oncology, 2021)
Background: For a majority of patients with metastatic colorectal cancer (mCRC) with MS stable (MSS) or mismatch repair proficient (pMMR), the role of immunotherapy is undetermined. This study investigated the efficacy and safety of camrelizumab when added to XELOX chemotherapy plus bevacizumab or regorafenib as first-line therapy for mCRC. Materials and Methods: Medical records of mCRC patients who received camrelizumab and XELOX plus bevacizumab or regorafenib at the First Hospital of Quanzhou Affiliated to Fujian Medical University between June 1, 2019, and April 30, 2021, were retrospectively collected. The objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and side effects of the drug were recorded and reviewed. Results: Twenty-five eligible patients received combination therapy,including bevacizumab in 19 patients and regorafenib in 6. Twenty-one patients had pMMR/MSS and one MSI-H. Of the 25 patients who could be evaluated for efficacy, 18 (72%) achieved PR, 6(24%) achieved SD, and 1(4%) achieved PD. The ORR and DCR were 72% (18/25) and 96% (24/25), respectively. The median progression-free survival (PFS) was 11.2 months (95% CI 8.9–13.9), and OS had not yet been reached. The combination regimen of regorafenib in six (24%) patients was unassociated with treatment outcomes. Most AEs were either grade 1 or 2, and treatment-related grade 3 toxicities were observed in 8/25 (32%) patients. Conclusion: Camrelizumab combined with XELOX plus bevacizumab or regorafenib was feasible, producing high rates of responses as first-line therapy in unselected Chinese patients with MSS mCRC. The toxicities were generally tolerable and manageable. Prospective randomized trials with large sample sizes are needed to evaluate these findings.